2017
DOI: 10.1111/bph.13870
|View full text |Cite
|
Sign up to set email alerts
|

The anaesthetized rabbit with acute atrioventricular block provides a new model for detecting drug‐induced Torsade de Pointes

Abstract: These results suggest that our model of the unremodelled and bradycardic heart of the anaesthetized rabbit is a useful test system for the detection of drug-induced TdP arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…In the chronic atrioventricular block monkey heart, each of the dl -sotalol-induced TdP spontaneously terminated, which is consistent with that reported for the acute atrioventricular block rabbit model ( Hagiwara et al, 2017 ); however, in the chronic atrioventricular block canine model, most of TdP degenerated into ventricular fibrillation ( Sugiyama, 2008 ; Smoczynska et al, 2019 ). In order to better understand underlying mechanism for spontaneous termination of TdP, we calculated “effective size of the heart ( I )” for spiral rotation ( Panfilov, 2006 ) using the formula: I = .…”
Section: Discussionsupporting
confidence: 87%
“…In the chronic atrioventricular block monkey heart, each of the dl -sotalol-induced TdP spontaneously terminated, which is consistent with that reported for the acute atrioventricular block rabbit model ( Hagiwara et al, 2017 ); however, in the chronic atrioventricular block canine model, most of TdP degenerated into ventricular fibrillation ( Sugiyama, 2008 ; Smoczynska et al, 2019 ). In order to better understand underlying mechanism for spontaneous termination of TdP, we calculated “effective size of the heart ( I )” for spiral rotation ( Panfilov, 2006 ) using the formula: I = .…”
Section: Discussionsupporting
confidence: 87%
“…Subgroup analysis in this study showed that glioblastoma patients with high hERG expression who received hERG blockers had improved survival ( P = 0.0458) whereas there was no difference in survival for low hERG–expressing glioblastoma patients who received hERG blockers ( P = 0.4136). Sparfloxacin is a fluoroquinolone antibiotic that was withdrawn from the market because, apart from its phototoxicity, it induced QT interval prolongation and torsade de pointes by inhibiting the hERG channel . A study with hERG‐transfected HEK293 cells and siRNA‐knock‐down HCT116 cells confirmed that sparfloxacin‐inhibited cell viability and this inhibition correlated with hERG expression.…”
Section: Resultsmentioning
confidence: 99%
“…Sparfloxacin is a fluoroquinolone antibiotic that was withdrawn from the market because, apart from its phototoxicity, it induced QT interval prolongation and torsade de pointes by inhibiting the hERG channel. [185][186][187][188][189][190] A study with hERG-transfected HEK293 cells and siRNA-knock-down HCT116 cells confirmed that sparfloxacin-inhibited cell viability and this inhibition correlated with hERG expression. When combined with 5-fluorouracil, sparfloxacin showed synergistic antiproliferation activity in HCT116 and HT-29 cells.…”
Section: Potential Use In Oncologymentioning
confidence: 99%
“…This relatively high heart rate leads to a reduced heart rate reserve, which limits the use of rabbits for the investigation of exercise-induced effects on the cardiovascular system (Milani-Nejad & Janssen, 2014). Partial solutions to this problem may be obtained by surgical ablation of the atrioventricular node (Hagiwara et al, 2017;Tsuji et al, 2006), although this may predispose the rabbit heart to arrhythmias. Other disadvantages of rabbits, compared to mice, are their relative high housing/breeding costs, lower reproduction rate and lower efficacy of genetic manipulation, which is outweighed by their high clinical relevance as cardiac disease models as highlighted in the following.…”
Section: Advantages and Disadvantages Of Animal Models Of Different Species For (Monogenic) Cardiac Disease Researchmentioning
confidence: 99%